Experimental Investigation on Strength and Water Permeability of Mortar Incorporate with Rice Straw Ash - Surajit Munshi; Richi Prasad Sharma (Advances in Materials Science and Engineering)
The utilization of various agricultural residue ash as a pozzolanic material has the potential to reduce both the environmental impact and cost associated with building materials. In this paper, the authors studied the strength and permeability of mortar using different percentages of rice straw ash (RSA) as cement replacement and the possibilities of using RSA as a pozzolanic material. Locally available rice straws were burnt at a temperature of 600°C and ground to make RSA. The chemical and physical properties of RSA were studied and the outcome shows that the ash contains about 76% of silica in it. This investigation further focused the strength and water permeability of mortar using RSA, which demonstrates that up to 10% replacement both the strength and permeability have a better result than that of control specimen.